Virtual Correlations in Single Qutrit - Alexey A. Strakhov; Vladimir I. Man’ko (Advances in Mathematical Physics)
We construct the positive invertible map of the mixed states of a single qutrit onto the antisymmetrized bipartite qutrit states (quasifermions). It is shown that using this one-to-one correspondence between qutrit states and states of two three-dimensional quasifermions one may attribute hidden entanglement to a single mixed state of qutrit.